2017
DOI: 10.1152/ajpgi.00169.2016
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and function of bone morphogenetic protein signaling in colonic injury and inflammation

Abstract: In this study we report a series of novel observations that underscore the importance of bone morphogenetic protein (BMP) signaling in the regulation of colonic homeostasis during the development of injury and inflammation. In particular, we present evidence that BMP signaling mitigates the response of the colonic epithelium to injury and inflammation and that cytokines, such as TNF-α and IL-1β, inhibit the expression of BMP-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Previous work in the colon and skin has suggested that physiological attenuation of the BMP pathway is required for regeneration 21,22 and this was consistent with our finding that autocrine ligand exposure impaired secretory cell dedifferentiation capacity. Next, we mapped the BMP signalling landscape in human inflammatory bowel disease (IBD) and two distinct mouse intestinal regeneration models ( Supplementary Fig.4a,b).…”
Section: Mapping the Bmp Signalling Landscape In Mouse And Human Colosupporting
confidence: 93%
“…Previous work in the colon and skin has suggested that physiological attenuation of the BMP pathway is required for regeneration 21,22 and this was consistent with our finding that autocrine ligand exposure impaired secretory cell dedifferentiation capacity. Next, we mapped the BMP signalling landscape in human inflammatory bowel disease (IBD) and two distinct mouse intestinal regeneration models ( Supplementary Fig.4a,b).…”
Section: Mapping the Bmp Signalling Landscape In Mouse And Human Colosupporting
confidence: 93%
“…Evidence indicated that the anticancer activity of HNK can also be mediated by upregulating p53 in CRC (14), but how HNK regulates p53 is unknown. Bone morphogenetic proteins (BMPs) belong to the transforming growth factor-β (TGF-β) super-family and plays an important role in regulating the proliferation and differentiation in epithelium of colon and rectum (17,18). The aberrant signal of BMPs has been involved in the cause and progress of CRC (19,20).…”
Section: Introductionmentioning
confidence: 99%
“… 44 , 45 The anti-inflammatory effect of BMP signaling was further substantiated by the observation that deletion of Bmpr1a in the colonic mucosa leads to enhancement of Dextran Sulfate Sodium-induced colonic injury and inflammation. 45 Finally, transgenic expression of BMP-4 in the skin of mice treated with both the carcinogen N-methyl-N′-nitrosoguanidine and the tumor promoter 12-O-tetradecanoylphorbol-13-acetate leads to a marked decrease in the degree of cellular hyperproliferation and inflammation induced by these agents. 46 The significance of these findings has been further confirmed by the observation that patients with inflammatory bowel disease can exhibit alterations in the TGF-β signaling cascade and that these abnormalities can render patients unable to mount an effective anti-inflammatory response in the gastrointestinal tract.…”
Section: Bone Morphogenetic Protein Signaling Regulates Gastric Inflamentioning
confidence: 99%
“…Moreover, BMP-7 appears to decrease the degree of inflammation seen during ischemic acute renal failure in rats 43 . Similarly, BMP-7 ameliorates the severity of colonic inflammation, and it accelerates the healing of colitis in rats exposed to trinitrobenzenesulfonic acid, a well-established inducer of experimental colitis in rodents 44, 45. The anti-inflammatory effect of BMP signaling was further substantiated by the observation that deletion of Bmpr1a in the colonic mucosa leads to enhancement of Dextran Sulfate Sodium-induced colonic injury and inflammation 45 .…”
Section: Bone Morphogenetic Protein Signaling Regulates Gastric Inflamentioning
confidence: 99%
See 1 more Smart Citation